Does investment in human resource development affect financial performance? Empirical evidence from the banking sector of Bangladesh - Bhuiyan, Mohammad Zahid Hossain; Uddin, Md Mahi; Ahmad, Afzal; Hoque, Nazamul (IIUC Studies, 2017)
The study aims at examining the impact of investment in human resource development (HRD) on the financial performance of the banking sector of Bangladesh. Using the economic data as well as survey data collected from purposively selected 120 bank executives of 20 private commercial banks of Bangladesh. The study through regression models finds that there is a significant positive correlations between HRD investment (in salaries and allowances, provident fund and gratuity, bonus and incentives, staff welfare and training, workshop, and seminar) and financial performance of the sample banks. Though, training is one of the important HRD indicators, the lowest investment was made in this sector by the sample banks. The findings of the study may be useful for bankers, policymakers, HR professionals, and the stakeholders of all types of organizations regardless of the geographical boundary. Finally, further investigations on manufacturing and other service sectors through case study, focus groups, and longitudinal study are also suggested. IIUC Studies Vol.14(2) December 2017: 35-54